Development of a multi-risk index for Italy: a tool for supporting informed decision making on disaster risk reduction - Tocchi, Gabriella; Polese, Maria; Galasso, Carmine; Cremen, Gemma; ICASP14 (My University, 2023)
Effective disaster-risk management decision making relies on holistic multi-risk quantification approaches. Such approaches capture the effects of multiple hazards, facilitating the development and implementation of appropriate preparedness and mitigation strategies. However, performing multi-risk assessments can be challenging, particularly at large geographic scales, because of the requirements in terms of input data and computational resources involved. Furthermore, these assessments typically fail to account for social vulnerability or diverse stakeholder risk priorities in related policy (or more general) decision making, which are crucial considerations. We propose a straightforward multi-risk index that overcomes the aforementioned challenges and limitations. We demonstrate it for earthquake and flood risk across the entire country of Italy (at the resolution of municipalities), using easily accessible data. The index appropriately accounts for uncertainties, relying on probabilistic distributions of hazard inputs, physical and social vulnerability indices, and population exposure for each individual risk of interest. The resulting individual risk scores are combined through suitable weights that explicitly reflect variable stakeholder perspectives. The proposed metric identifies hotspots across the Italian territory that should be prioritised for actions that promote disaster risk reduction. Sensitivity analyses of metric weights reveal how these hotspots can change as a function of stakeholder priorities and single risk considerations, ultimately underlining the importance of accounting for accurate stakeholder feedback and a holistic view of risk in disaster-related decision making. A prominent advantage of the proposed index is that it is relatively simple and could be easily adopted for effective multi-risk decision support across any other national o transnational context of interest.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED